2015
DOI: 10.1155/2015/398156
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome: Yoga as Remedial Therapy

Abstract: Irritable bowel syndrome (IBS) is a group of symptoms manifesting as a functional gastrointestinal (GI) disorder in which patients experience abdominal pain, discomfort, and bloating that is often relieved with defecation. IBS is often associated with a host of secondary comorbidities such as anxiety, depression, headaches, and fatigue. In this review, we examined the basic principles of Pancha Kosha (five sheaths of human existence) concept from an Indian scripture Taittiriya Upanishad and the pathophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…One descriptive review on yoga for IBS was available, which concluded that the essential components of a yoga module for IBS should include postures, breathing, and meditation and should be designed to be easily practiced by most patients, with least complications. 44 This review included 2 RCTs that were also included in our review 36,39 and a trial that observed that any moderate physical activity 3 times a week ranging from 20 to 60 minutes improved symptom severity of IBS when compared with nonactive control subjects. 43 A long-term follow-up also showed improvement in disease-specific quality of life, fatigue, depression, and anxiety.…”
Section: Agreements With Prior Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…One descriptive review on yoga for IBS was available, which concluded that the essential components of a yoga module for IBS should include postures, breathing, and meditation and should be designed to be easily practiced by most patients, with least complications. 44 This review included 2 RCTs that were also included in our review 36,39 and a trial that observed that any moderate physical activity 3 times a week ranging from 20 to 60 minutes improved symptom severity of IBS when compared with nonactive control subjects. 43 A long-term follow-up also showed improvement in disease-specific quality of life, fatigue, depression, and anxiety.…”
Section: Agreements With Prior Systematic Reviewsmentioning
confidence: 99%
“…50 It was hypothesized that yoga addresses the brain-gut axis in the management of IBS with fewer side effects than conventional treatment. 44…”
Section: Modes Of Actionmentioning
confidence: 99%
“…The yoga philosophy component (see Table 4) was based on relevant contemplative and reflective practices from Patañjali Yoga Sūtras that focused on self-study, personal development, observances, yamas (ethical discipline), and attitudes of acceptance, among others [4, 64, 66]. Concepts found in classical scripture, such as the kośas theory of self, are being integrated in protocols for yoga interventions for chronic illness with a mind-body component [67]. The classes were one-third āsana, one-third relaxation training, and one-third yoga philosophy.…”
Section: Methodsmentioning
confidence: 99%
“…Yoga is an ancient practice involving physical and mind activities, which may improve physical and psychological wellness and regulates autonomic imbalance 69 . Although depending on technic, time, and intensity, yoga as physical activity produces an average energy expenditure close to three METs 70 .…”
Section: Exercise Associated With Specific Skills or Knowledgementioning
confidence: 99%